Analisis Daya Dukung Fondasi Tiang Dengan Perkuatan Model Sayap Pada Tanah Lunak - Irfan Hasan; Ferry Fatnanta; Soewignjo Agus Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Advancements in science and technology of civil engineering have led the development of modifications to the shape of pile foundation. Modification of the pile foundation by adding wings to the pile is one way to increase skin friction on soft soil, so that a greater bearing capacity is obtained. In this research, piles were modeled with variations of wing’s lengths of 0.50D, 0.75D, 1.00D, and 1.25D, the distance between wings also varies from 3D, 6D, and 9D. Constant Rate of Penetration (CRP Test) will be used as a method for loading test. The bearing capacity based on loading test data will be analyzed using Terzaghi and Peck method Analysis results showed that winged foundations were able to bearing greater loads than normal piles. The largest pile bearing capacity occurs in pile models with wing lengths of 1.25D and distance of 3D (TS2-1.25D-3D). Addition of wing length until 1.25D will always improve the piles bearing capacity. Unlike wing’s length, addition of the distance between the wings until 9D not always improve the piles bearing capacity. Keywords: Bearing capacity, Constant Rate of Penetration, soft soil, Terzaghi and Peck method, winged foundation